Hemodynamic Changes After Left Ventricular Assist Device Implantation Among Heart Failure Patients With and Without Elevated Pulmonary Vascular Resistance - Grupper, Avishay; Mazin, Israel; Faierstein, Kobi; Kurnick, Adam; Maor, Elad; Elian, Dan; Barbash, Israel M.; Guetta, Victor; Regev, Ehud; Morgan, Avi; Segev, Amit; Lavee, Jacob; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular assist devices (LVADs) may reverse elevated pulmonary vascular resistance (PVR) which is associated with worse prognosis in heart failure (HF) patients. We aim to describe the temporal changes in hemodynamic parameters before and after LVAD implantation among patients with or without elevated PVR. Methods HF patients who received continuous-flow LVAD (HeartMate 2&3) at a tertiary medical center and underwent right heart catheterization with PVR reversibility study before and after LVAD surgery. Patients were divided into 3 groups: normal PVR (<4WU); reversible PVR (initial PVR ≥4WU with positive reversibility); and non-reversible (persistent PVR ≥4WU). Results Overall, 85 LVAD patients with a mean age of 58 years (IQR 49–64), 65 patients (76%) were male; 60 patients had normal PVR, 20 patients with reversible and 5 patients with non-reversible PVR pre-LVAD. All patients with elevated PVR (≥4WU) had higher pulmonary pressures (PP) and increased trans-pulmonary gradient (TPG) compared to patients with normal PVR (p < 0.05). Patients with non-reversible PVR were more likely to have a significantly lower baseline cardiac output (CO) compared to all other groups (p ≤ 0.02). Hemodynamic parameters and PVR post LVAD were similar in all study groups. Patients with baseline elevated PVR (reversible and non-reversible) demonstrated a significant improvement in PP and TPG compared to patients with normal baseline PVR (p ≤ 0.05). The improvement in CO and PVR post-LVAD in the non-reversible PVR group was significantly greater compared to all other groups (p < 0.01). There were no significant differences between study groups in post LVAD and post heart transplantation course. Conclusion Hemodynamic parameters improved after LVAD implantation, regardless of baseline PVR and reversibility, and enabled heart transplantation in patients who were ineligible due to non-reversible elevated PVR. Our findings suggest that mitigation of elevated non-reversible PVR is related to reduction in PP and increase in CO.